Event structure - Van Voorst, Jan (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1988)
This study establishes a relation between the semantics of the subject and the direct object-NP and aspect. The notion of event is central. Events have a beginning and an end. This means in temporal terms that events have a point in time at which they begin and a point in time at which they end. However, events are not defined in temporal terms but in spatial terms. This means that they are defined in terms of the entity that can be used to identify their beginning and the entity that can be used to identify their end. These two entitites are denoted by the subject and the direct object-NP resp.